2004
DOI: 10.1046/j.1365-2133.2003.05729.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel treatment of chronic severe hand dermatitis with bexarotene gel

Abstract: Bexarotene gel appears to be safe, tolerated by most patients, with useful therapeutic activity in chronic severe hand dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…7,19 A hypothesis of retinoid X receptor-mediated activity is supported by the activity of bexarotene, a retinoid X receptor agonist, applied topically as a 1% gel twice daily or 3 times daily in patients with severe CHaD. 20 However, at present, the therapeutic effect of alitretinoin cannot be explicitly linked to a particular pattern of receptor binding and consequent biological effects. 7 The encouraging results of this trial support further clinical studies of alitretinoin in the treatment of patients with CHaD.…”
Section: Commentmentioning
confidence: 99%
“…7,19 A hypothesis of retinoid X receptor-mediated activity is supported by the activity of bexarotene, a retinoid X receptor agonist, applied topically as a 1% gel twice daily or 3 times daily in patients with severe CHaD. 20 However, at present, the therapeutic effect of alitretinoin cannot be explicitly linked to a particular pattern of receptor binding and consequent biological effects. 7 The encouraging results of this trial support further clinical studies of alitretinoin in the treatment of patients with CHaD.…”
Section: Commentmentioning
confidence: 99%
“…A study concluded that topical bexarotene had potential use in severe chronic hand dermatitits. A high rate of treatment-related irritation was reported (29 %) [77]. Oral acitretin led to 50 % average improvement in the clinical score in patients with tylotic eczema for 4 weeks, with no additional improvement with longer treatment.…”
Section: Retinoidsmentioning
confidence: 97%
“…Pertinent to hyperproliferative cutaneous conditions, bexarotene has antikeratinizing activity as a topical agent and has been shown to cause thinning of the stratum corneum in the rhino mouse model [8]. It has also been hypothesized that bexarotene decreases inflammation through interaction with PPARs, which may reduce inflammatory cytokine expression [8,9]. Bexarotene can also inhibit T-cell accumulation in CTCL [8].…”
Section: Discussionmentioning
confidence: 99%
“…These receptors homodimerize and bind DNA to affect the function of genes downstream of retinoid acid response elements (RAREs) [7]. Additionally, RXRs have the unique capacity to heterodimerize with other classes of nuclear receptors, including RARs, vitamin D receptor (VDR), thyroid receptor (TR), and peroxisome proliferation activating receptors (PPARs) [8,9]. Therefore, retinoids that bind RXRs, also known as "rexinoids," can affect a variety of cellular pathways.…”
Section: Discussionmentioning
confidence: 99%